Aumento de rebordo ósseo alveolar utilizando peptídeo de união celular (P-15) associado a derivado de osso bovino inorgânico. estudo clínico e histológico - Souza, Rogério Oliveira de (2003)
Osteoinduction has been attempted by several means to treat osseous defects. Some clinical studies have demonstrated that a synthetic cell binding peptide with anorganic bovine derived bone matrix has the ability to enhance bone regeneration. These studies have suggested that more histological data is necessary to better understand this process. The objective of this study was to evaluate clinically and histologically the use of this material associated or not with a bioabsorbable membrane to regenerate localized chronic alveolar ridge defects. Six adult, male mongrel dogs were used in this study. Bilateral, class III, alveolar defects were surgically produced following extraction of the mandibular second premolar teeth. After an 8-week healing interval, mucoperiosteal flaps were elevated. The material associated or not with resorbable membrane was implanted into contralateral defects in 10 sites. Two sites received no biomaterial to serve as controls. Mucoperiosteal flaps were advanced over the constructs and sutured. Clinical evaluation pre and post-augmentation was made utilizing periodontal probe and caliper. The animals were euthanised at 12 weeks post-augmentation and block specimens processed for histologic evaluation. Clinical results showed no significant statistical augmentation on the control group (0.0 ± 0.6 mm). In all experimental sites, whith and whithout resorbable membrane, relevant ridge augmentation was observed (2.9 ± 1.9 mm and 3.6 ± 2.0 mm, respectively). Histologically, all experimental sites showed active bone formation with plump osteoblast and osteoid matrix deposition. Bone ingrowth filled the area of the defects treated with the material associated to the membrane. Few particles were seen in the cellular fibrous tissue surrounding the new formed bone trabeculae. The material with or without membrane can produce a significant clinical ridge augmentation. Bone formation was histologically observed in all test areas. The association of a membrane seemed to enhance the process of bone formation